2006
DOI: 10.1097/01.ico.0000183490.16131.e3
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Analysis In Vitro of Ethyl-cyanoacrylate Against Ocular Pathogens

Abstract: The ethyl-cyanoacrylate has bacteriostatic and bactericidal action in vitro, mainly against gram-positive microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 10 publications
1
24
0
3
Order By: Relevance
“…Dental cyanoacrylates yielded the first observations of such antibacterial properties 12–14. Refojo et al reported using cyanoacrylates to manage corneal perforations in the 1960s and later generated similar conclusions 15 16. Surgical applications of cyanoacrylates shortly followed 17…”
Section: Introductionmentioning
confidence: 84%
“…Dental cyanoacrylates yielded the first observations of such antibacterial properties 12–14. Refojo et al reported using cyanoacrylates to manage corneal perforations in the 1960s and later generated similar conclusions 15 16. Surgical applications of cyanoacrylates shortly followed 17…”
Section: Introductionmentioning
confidence: 84%
“…36,37 Cyanoacrylate glues can also prevent the development of the critical setting for collagenase production that leads to stromal melting, and has a significant bacteriostatic activity against gram-positive organisms. 38,37 The major concern is toxicity of cyanoacrylate through direct contact with the corneal endothelium and lens. The efficacy of N-butyl-2-cyanoacrylate in corneal perforations was also compared with fibrin glue in a randomized clinical trial.…”
Section: Cyanoacrylate Gluesmentioning
confidence: 99%
“…The use of filter paper discs on the evaluation of antimicrobial activity is proven to be a very easy method, with high sensitivity and specificity, since it analyzes solely the effect of the studied substance in direct and homogeneous contact with the microorganisms in growth. Other authors have chosen this method to assess the antimicrobial activity of different substances used daily in clinical and surgical practice, such as trypan blue, fluorescein and cyanoacrylate, obtaining reliable results (32)(33)(34) . Through this method, we did not observe the presence of inhibition halos around the paper filter discs soaked with silicon oil in any of the plates containing the different concentrations of bacterial inocula, suggesting that the silicon oil at 1000 cps does no have any effect on in vitro bacterial growth.…”
Section: Discussionmentioning
confidence: 99%